A study of the relationship of authoritarianism and achievement in a Jamaican teachers' college - Anderson, Laurence Ernest (1972)
This study sought to investigate the relationship of authoritarianism and achievement by first-year students of Church Teachers' College, Mandeville, Jamaica. The California F Scale of Authoritarianism was administered to the same group of students at intervals during their three-year course of study. It was found that: 1) low scoring students (less authoritarian) did not change significantly during their stay in college; 2) of the high scoring students, some became less authoritarian during their college stay, but some did not; and 3) low scores on the F scale were significantly related to success at college: the final college grades of students were used as the criterion measure. It was concluded that some students had very deep-seated authoritarian personalities, and that the college environment did not provide sufficient encouragement for the adoption of non-authoritarian views
Keywords: Academic achievement